Release and Activity of Matrix Metalloproteinase-9 and Tissue Inhibitor of Metalloproteinase-1 by Alveolar Macrophages from Patients with Chronic Obstructive Pulmonary Disease - Russell, Richard E. K; Culpitt, Sarah V; DeMatos, Carmen; Donnelly, Louise; Smith, Michael; Wiggins, John; Barnes, Peter J (American journal of respiratory cell and molecular biology, 2002)
Destruction of lung elastin is critical for development of emphysema associated with chronic obstructive pulmonary disease (COPD). Lung macrophages release elastolytic enzymes, including matrix metalloproteinase (MMP)-9, along with tissue inhibitors of MMP (TIMP). We examined the production and activity of macrophage-derived MMP-9 and TIMP-1 from alveolar macrophages (AM) from smokers with COPD, healthy smokers (HS), and nonsmokers (NS). AM were stimulated with either lipopolysaccharide (LPS), interleukin (IL)-1 beta, or cigarette smoke-conditioned culture medium (CSM). AM from patients with COPD released greater amounts of MMP-9 with greater enzymatic activity than HS and NS. In contrast, AM from NS released more TIMP-1 than cells from HS and subjects with COPD. LPS and IL-1 beta caused a dose-dependent increase in MMP-9 release and activity, together with increased levels of TIMP-1. Dexamethasone prevented the increase in MMP-9 release, and increased TIMP-1 release. CSM increased MMP-9 and TIMP-1 release from AM of all groups. Dexamethasone decreased CSM-stimulated MMP-9 release, but had no effect on MMP-9 activity This study suggests that macrophages might be important in the development of COPD because these cells exhibit increased levels of elastolytic activity.